CHEFSYNC (CIPEEX, 2024)
CHEFSYNC" IS AN APPLICATION PROJECT IN THE EARLY STAGES OF DEVELOPMENT THAT SEEKS TO TRANSFORM THE HOME COOKING EXPERIENCE THROUGH THE INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI). THE MAIN OBJECTIVE OF THIS CASE STUDY IS TO ELUCIDATE THE DEVELOPMENT STRATEGIES, AI IMPLEMENTATION METHODS AND FUNCTIONALITIES PLANNED FOR THE APP. THE AI IS DESIGNED TO ANALYZE USERS' CONSUMPTION PATTERNS AND FOOD PREFERENCES, USING MACHINE LEARNING ALGORITHMS TO RECOMMEND PERSONALIZED RECIPES AND MANAGE FOOD INVENTORY. IN ADDITION, THE APP AIMS TO REDUCE FOOD WASTE BY SUGGESTING RECIPES THAT USE INGREDIENTS ALREADY AVAILABLE IN THE USER'S STORAGE. THE DEVELOPMENT METHOD ADOPTED FOLLOWS AN AGILE APPROACH, ALLOWING FOR CONTINUOUS ADJUSTMENTS AND IMPROVEMENTS BASED ON USER FEEDBACK AND TEST RESULTS. SO FAR, PRELIMINARY RESULTS INDICATE HIGH ACCEPTANCE OF THE CONCEPT, WITH THE POTENTIAL TO EFFECTIVELY MINIMIZE FOOD WASTE AND IMPROVE EFFICIENCY IN MEAL PREPARATION. IN THE FUTURE, THE PROJECT HAS AMBITIOUS PLANS TO INTEGRATE WITH SUPERMARKET CHAINS TO AUTOMATE THE PROCESS OF BUYING INGREDIENTS, BASED ON THE USER'S STOCK LEVELS. THIS FUNCTIONALITY WILL NOT ONLY MAKE THE COOKING EXPERIENCE MORE CONVENIENT, BUT ALSO HAS THE POTENTIAL TO REVOLUTIONIZE THE WAY PEOPLE INTERACT WITH THE FOOD ECOSYSTEM. IN CONCLUSION, "CHEFSYNC" REPRESENTS A SIGNIFICANT INNOVATION AT THE INTERSECTION OF TECHNOLOGY AND COOKING, WITH A STRONG FOCUS ON PERSONALIZATION AND SUSTAINABILITY. THE PROJECT IS AT AN EARLY STAGE, BUT ALREADY DEMONSTRATES CONSIDERABLE POTENTIAL TO POSITIVELY IMPACT USERS' DAILY LIVES AND EATING HABITS
Keywords: Artificial Intelligence; Food Management; Automatic Purchasing; Waste Reduction